1998
DOI: 10.1149/1.1838632
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Crevice‐Opening Dimension on the Stability of Crevice Corrosion for Nickel in Sulfuric Acid

Abstract: The role of the crevice-opening dimension, a, on the stability of crevice corrosion was investigated in the Ni/i N H2S04 system. The electrode potential and current distributions inside the crevice were measured and calculated, respectively. Other variables, in particular the composition of the electrolyte, were constrained from changing during the experiment. The passive/active boundary, x ass' moved further into the crevice for increasing a, and was in close agreement with the calculated value using the IR =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
57
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 5 publications
8
57
0
Order By: Relevance
“…The scan rate was 0.08 mV s À1 active region of the crevice electrolyte polarization curve [4,9]. This is also consistent with recent work by Abdulsalam and Pickering [2] where it was shown that the crevice gap of 0.4 mm is the upper limit for crevice corrosion to start in 1N sulfuric acid. For the system discussed here, the results predict that an increase in the acid concentration enhances the crevice corrosion rate action manifested by the increase in the total cell current.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The scan rate was 0.08 mV s À1 active region of the crevice electrolyte polarization curve [4,9]. This is also consistent with recent work by Abdulsalam and Pickering [2] where it was shown that the crevice gap of 0.4 mm is the upper limit for crevice corrosion to start in 1N sulfuric acid. For the system discussed here, the results predict that an increase in the acid concentration enhances the crevice corrosion rate action manifested by the increase in the total cell current.…”
Section: Discussionsupporting
confidence: 89%
“…It is interesting to see that the location is directly at the transition point between the passive and active region of the polarization curve indicating a close agreement between the polarization curve and the behavior of the crevice corrosion inside the cavity. This is in lieu of the IR drop mechanism which predicts similar phenomenon [1,2,6,8,10].…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…The first, addresses the change in the chemical composition of the electrolyte and the formation of a critical crevice solution with concentrations of H þ and Cl À that are large enough to breakdown the passive film [3]. The other theory is the IR voltage drop theory which attributes crevice corrosion to a significant ohmic drop that shifts the potential within the crevice to the active region of the polarization curve for the given metal/electrolyte system [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%